Differential promoter methylation of DAZL gene in bulls with varying seminal parameters. (31st March 2018) - Sarova, N; Ahlawat, S; Grewal, A; Sharma, R; Arora, R
Contents: In India, cross‐breeding of indigenous cattle with exotic cattle such as Holstein Friesian and Jersey has been going on since last four decades to improve milk production. Although it has led to increased milk yield, the subfertility in male cross‐bred progeny has remained a significant problem. Epigenetic modifications (DNA methylation, histone modifications and chromatin remodelling) are regarded as key players influencing gene expression. DAZL gene plays an important role in germline development and gametogenesis. The methylation and mRNA expression level of this gene have been significantly negatively correlated in the testes of cattle–yak hybrids and their parents. This study analysed the methylation profile of DAZL gene promoter in bull spermatozoa in an attempt to speculate its role in cross‐bred cattle subfertility. Semen samples from Sahiwal, Holstein Friesian and Frieswal bulls (Sahiwal X Holstein Friesian) with varying semen motility parameters were collected, and DNA was isolated. Methylation‐specific primers were used to amplify part of promoter and exon 1 of DAZL gene using bisulphite‐converted DNA. The amplified products were sequenced after cloning in pTZ57R/T vector. Sequence analysis revealed significantly higher DNA methylation of  DAZL  gene in Frieswal bulls with poor motility (28.26%) as compared to medium (15.21%) and high motility phenotype (6.52%). In pure‐bred counterparts, Sahiwal and Holstein Friesian, epigenetic marks were more in the former (15.21%) than the latter (4.34%), but in both cases, the values were lower as compared to the poor motility Frieswal bulls. This suggests that differential hypermethylation of the CpG islands could possibly influence reproductive parameters in bovines.